Workplace Environment and Employee Performance in Local Governments in Uganda: A Case of Kabale District Local Government. - Gasengayire, Sarah (Kabale University, 2024)
The research focused on Kabale District Local Government in Uganda and examined the connection between workplace environment and employee performance in local governments throughout Uganda. The research was directed by a set of objectives which included: to evaluate how organizational environment is associated with employee performance in Kabale District Local Government; to establish how the human environment is linked to employee performance in Kabale District Local Government; and to examine how the technical environment in Kabale District Local Government associated with performance of its employees. The research employed a cross-sectional research design and selected a sample of 146 participants through purposive and simple random sampling methods. The study used questionnaires and interview guide to collect data which was later analyzed using SPSS software that helped to generate descriptive and inferential statistical data and thematic analysis for qualitative data. The findings of the study indicated the Pearson correlation coefficient of r=.994**) which reveals a positive significant relationship between organizational environment and employee performance. The findings indicated a correlation results of (r=.905**) which revealed that human environment has a high positive significant relationship with employee performance. The study revealed that there was a positive significant relationship between technical environment and employee performance in Kabale District Local Government as indicated by a Pearson linear correlation coefficient (r) of .934** with a p-value of .000. The research findings indicated a significant positive association between organizational environment and employee performance. The research findings indicated that human environment has a high positive significant relationship with employee performance. The study recommended that Kabale District should always set targets to be achieved by each and every staff within a specific period of time and the necessary resources should be provided to all staff to aid them in the process. The study also recommended that the Ministry of Local Government and individual local governments should continue to strengthen the setting of standards and procedures to be followed by local government in performing their work. Kabale District Local Government should embrace building of teamwork to ensure that members of staff learn from each other on how to do things and devise means of executing their tasks. The study further recommended that there was always need for effective teamwork communication and the management of the local government and the Ministry of Local Government should always communicate effectively to the local government staff. Finally, the study recommended that employees should always be given the necessary and right equipment to help them perform their jobs.